Difficulties Faced by Master’s Students Doing the English Admission Test in the Area of ’’Everyday English’’‎‎‎‎‎ ‎"A Case Study of the Higher Institute of Languages, Tishreen University"‎‎‎‎‎ - Saker, Atef (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
‎The Master’s stage has its importance in development and intellectual building. However, in the process of applying for Master’s studies, applicants must pass the English Admission Test. When doing this test, master’s students encounter difficulties in the area of everyday English. ‎‎‎‎‎ ‎‎‎‎‎This research deals with the difficulties that master’s students may face in the area of everyday or spoken English. It is from the perspective of a sample of students doing a language course that can help them do the final English admission test at the Higher Institute of languages, Tishreen University. In order to achieve this goal, a questionnaire has been designed to investigate into difficulties faced by those students in the area of everyday English. After conducting the study and analysis, the research arrived at the following results:‎ 1- Master’s students doing the English admission test suffer from difficulties in idioms, the way they are written, and their use. In addition to that, there are anxieties when dealing with phrasal verbs and sayings that reflect the cultural aspects of the English society. Furthermore, there are problems with understanding English conversations. 2- ‎There are no varieties with statistical significance in the area of everyday English according to the sample of students in regard to the variables of gender and age.‎‎‎‎‎ 3- ‎Among the views of the sample of students, there exists no relation at a significance in everyday English that can be attributed to the variable of the stage of English acquisition.